2008
DOI: 10.1254/jphs.fp0071268
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Vasorelaxant Action of Angiotensin II in the Isolated Rat Renal Artery

Abstract: Abstract. Taking into consideration that mechanisms involved in the vasodilatator actions of angiotensin II have not yet been completely elucidated, the present study was undertaken in order to examine the mechanisms underlying the angiotensin II-induced relaxation of rat renal artery (RRA). Angiotensin II produced concentration-dependent and endothelium-independent relaxation of isolated RRA. Angiotensin II-induced relaxation was partially reduced by inhibitors of nitric oxide synthase and guanylyl cyclase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…Indomethacin, a COX pathways inhibitor, neither affected the relaxation to ACh of ILA, nor influenced the difference in the ACh response between H/R and control. This observation is in line with findings in isolated rat renal arteries and isolated perfused rat afferent arterioles ( Wang et al, 2003 ; Grbovic et al, 2008 ). In contrast, experiments in anesthetized rats revealed a 20–40% contribution of the indomethacin inhibited systems to the control of renal perfusion ( Dautzenberg and Just, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Indomethacin, a COX pathways inhibitor, neither affected the relaxation to ACh of ILA, nor influenced the difference in the ACh response between H/R and control. This observation is in line with findings in isolated rat renal arteries and isolated perfused rat afferent arterioles ( Wang et al, 2003 ; Grbovic et al, 2008 ). In contrast, experiments in anesthetized rats revealed a 20–40% contribution of the indomethacin inhibited systems to the control of renal perfusion ( Dautzenberg and Just, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, results on whether endothelium is involved in mediating the relaxation response of Ang II varied, because some reported that endothelium was involved [28][29][30][31][32] whereas others had found that endothelium was not involved [27,33]. Most of the studies had reported that stimulation of AT 2 receptors was involved in mediating the relaxation response [34]. Obviously, differences in the type of vessels and animal species may be some of the contributing factors in such contradicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Most of the above-mentioned adverse actions of Ang II are mediated by AT1 receptors, which are widely expressed by most cell types. Previous results of Grbovic et al 25 have shown that activation of B2Rs contributes to Ang II-induced relaxation of isolated rat renal artery via NO/cGMP pathway. The precise mechanism underlying interaction between Ang II and B2Rs still remains unclear and angiotensin type 2 receptors may be involved.…”
Section: Discussionmentioning
confidence: 86%